1984
DOI: 10.1021/jo00176a001
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and mechanistic studies of the electron-transfer-initiated photoaddition reactions of allylsilane-iminium salt systems

Abstract: Exploratory studies have uncovered novel photoaddition reactions occurring upon irradiation of 1-methyl-2-phenyl-l-pyrrolinium perchlorate (4) in the presence of a variety of allylsilanes 5-10 and leading to production of 2-allylpyrrolidine photoadducts. Mechanistic studies demonstrate that the reactions occur from the singlet excited state of 4. The effects of substituents on the allylsilane component on the reaction quantum efficiencies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…This process increases the rate of heterolytic fragmentation and has been proven to be a useful method for the generation of radicals for synthetic purposes. 1b,e-i,m The most common reaction of cation radical intermediates is α-heterolytic fragmentation with loss, or transfer to the solvent or to a nucleophile, of an electrofugal group (X + ), as shown in Scheme . Arene cation radical α-deprotonation, , desilylation, , and decarboxylation are the most common fragmentations of this type. Most studies in this area have been devoted to deprotonation and are based on product distribution analysis, ,,6a or the measurement of absolute rates ,6d,, and their response to variations in base strength or to steric and electronic effects.…”
Section: Introductionmentioning
confidence: 99%
“…This process increases the rate of heterolytic fragmentation and has been proven to be a useful method for the generation of radicals for synthetic purposes. 1b,e-i,m The most common reaction of cation radical intermediates is α-heterolytic fragmentation with loss, or transfer to the solvent or to a nucleophile, of an electrofugal group (X + ), as shown in Scheme . Arene cation radical α-deprotonation, , desilylation, , and decarboxylation are the most common fragmentations of this type. Most studies in this area have been devoted to deprotonation and are based on product distribution analysis, ,,6a or the measurement of absolute rates ,6d,, and their response to variations in base strength or to steric and electronic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Mariano and his coworkers developed the intra-and intermolecular photoadditions of the radical cations and the radicals derived from them to the = N-C ° radical [130][131][132]. Although they are summarized in his review article [3,[133][134][135], some examples are shown in Scheme 44.…”
Section: Addition To C = X Bondsmentioning
confidence: 99%
“…Mariano (1983aMariano ( , 1983b has ably reviewed the topic. Certain silicon containing iminium salts undergo p.e.t.-induced desilylation (Chen et al, 1983;Ohga et al, 1984). Allenes photoadd to 2-phenyl-1-pyrrolinium perchlorate (Somekawa et al, 1984).…”
Section: Organic Compoundsmentioning
confidence: 99%